Analysis of Fitness Status Variations of Under-16 Soccer Players Over a Season and Their Relationships With Maturational Status and Training Load - Nobari, Hadi; Silva, Ana Filipa; Clemente, Filipe Manuel; Siahkouhian, Marefat; García-Gordillo, Miguel Ángel; Adsuar, José Carmelo; Pérez-Gómez, Jorge (Frontiers in Physiology, 2021)
The purposes of this study were: (i) to analyze the variations of maximal oxygen consumption (VO2max), maximal heart rate (HRmax), heart rate rest, acceleration, maximal speed, agility, anaerobic sprint test (RAST) of peak power (RPP), RAST of minimum power, RAST of average power (RAP), and RAST of fatigue index (RFI) during the competition season, using maturation status (MS) and accumulated training load (ATL) as covariates; (ii) to describe differences between responders and non-responders in relationship with baseline levels. Twenty-three elite players of the same team competing in the national under-16 competitions were evaluated for 20 weeks in period 1 (P1= Before league), middle (Mid= mid league), and period 2 (P2= After league). Significant improvements were noticed in VO2max, RPP and RAP between P1 and Mid, with small, moderate and trivial effect sizes, respectively. Between Mid and P2 and in the entire period of evaluation, increases in maximal speed, RAP (both with small effect sizes), RPP and RFI (both with moderate effect sizes) were registered. When analyzing responders and non-responders, only HRmax (between P1 to P2) showed no differences between those groups. All these variables seemed to be influenced by ATL and MS, since when included as covariates, the differences were vanished. Additionally, almost all variables presented differences between responders and non-responders highlighting the individual responses to training.